A Study on Mechanical Behavior of Coconut Fiber Composite as an Alternative Material for Mobile Phone Housing - Muftil Badri (Proksima, 2023)
Mobile phone is one of the most widely used electronic products. Housing is part of a very important component of mobile phone. Mobile phone housing refers to the outer housing of the device that encompasses its internal components. Mobile phone housing materials have been widely developed, such as polyester, polyurethane, carbon fiber, wood and leather. This paper proposes to conduct tensile tests and fabrication of mobile phone housing to determine the mechanical characteristics of coconut fiber composites as an alternative material for mobile phone product. Finite element simulation of drop test is then conducted to determine the impact robustness of a product. The investigation of tensile characteristics was carried out using variations in fiber direction. Vacuum assisted resin infusion is used as a method for manufacturing mobile phone housing product. Finite element simulation of mobile phone housing with various drop test positions was also conducted and the impact behaviour of coconut fiber composite housing materials was also obtained. It was shown that coconut fiber can be used as an alternative material for mobile phone housing. The design of the mobile phone housing also needs to be considered at the corner position of the housing because this is the location where the maximum impact stress occurs.